Expression of matrix metalloproteinases (MMPs)−2/-7/-9/-14 and tissue inhibitors of MMPs (TIMPs)−1/-2 in bovine cutaneous fibropapillomas associated with BPV-2 infection - Daraban Bocaneti, Florentina; Altamura, Gennaro; Corteggio, Annunziata; Tanase, Oana Irina; Dascalu, Mihaela Anca; Pasca, Sorin Aurelian; Hritcu, Ozana; Mares, Mihai; Borzacchiello, Giuseppe (Frontiers in Veterinary Science, 2022)
Bovine papillomaviruses -1/-2 (BPVs) are small non-enveloped double-stranded DNA viruses able to infect the skin of bovids and equids, causing development of neoplastic lesions such as bovine cutaneous fibropapillomas and equine sarcoid. Matrix metalloproteinases (MMPs) are a group of zinc-dependent endopeptidases that degrade basal membrane and extracellular matrix, whose function is essential in physiological processes such as tissue remodeling and wound healing. MMPs activity is finely regulated by a balancing with expression of tissue inhibitors of MMPs (TIMPs), a process that is impaired during tumour development. BPV infection is associated with upregulation of MMPs and /or their unbalancing with TIMPs, contributing to local invasion and impairment of extracellular matrix remodeling in equine sarcoid; however, studies regarding this topic in bovine fibropapillomas are lacking. In this work, we aimed at performing an immunohistochemical and biochemical analysis on a panel of MMPs and TIMPs in BPV-2 positive bovine cutaneous fibropapillomas vs normal skin samples. Results from immunohistochemistry and western blotting revealed overexpression of MMP-2/-7/-9 along with down-regulation of MMP-14, accompanied by a decrease in TIMP-1/-2 levels in tumour versus normal skin samples. Moreover, gelatine zymography confirmed the expression of pro-active MMP-2 and MMP-9 and, most importantly, indicated the presence and increased activity of their active forms (82 and 62 kDa, respectively) in tumour samples. This is the first study describing MMPs and TIMPs in bovine cutaneous fibropapillomas and our results suggest that their unbalanced expression in presence of BPV-2 may play a significant role in tumour development.